COLEÓPTEROS DE FOLLAJE DE LA RESERVA NACIONAL RÍO CLARILLO (CHILE CENTRAL) - Solervicens, Jaime; Estrada, Patricia (Acta Entomológica Chilena, 2022)
A study of the foliage Coleóptera from the Río Clarillo National Reserve, Central Chile, was carried on. Samples were taken every month between May 1991 to June 1992. The sampling method employed was the beating sheet. The fourteen most characteristic trees and shrubs were selected to investígate their fauna. 125 species from 27 families of Coleóptera were recognized. Springtime showed the more abundante and richness of species. Although the larger number of Coleóptera haven’t any special association with the plants, 11 phytophagous species appear more or less strictly related to 7 species of plants. Two groups of species are distinguished after their vegetational preferences: species on evergreen plants and species on summer deciduous plants.